From planning to implementation: explaining connections between adaptive management and population models - Lahoz-Monfort, José J.; Guillera-Arroita, Gurutzeta; Hauser, Cindy E. (Frontiers in Ecology and Evolution, 2014)
The management of natural systems often involves periodic interventions that must be decided without a complete understanding of how the system responds to our actions. It is in this situation of recurrent decision-making under uncertainty that adaptive management (AM) has been repeatedly advocated, with each decision round providing an opportunity to improve our knowledge in order to facilitate future decisions: the ‘learning while managing’ tenet of AM. When the subject of management is a wildlife population (that is harvested, is a pest or is threatened with extinction), population models will be at the core of the AM process. We provide an overview of the steps in AM, from the set-up to the iterative phase, highlighting the central role that population models can play at different stages of the process of planning and implementing an AM program, as well as when analyzing the value of acquiring new information. We discuss the contexts in which these models have been applied in natural resource management and biodiversity conservation. We aim to bring this applied discipline to the attention of researchers interested in population dynamics, while stressing the relevance of these models for managers considering an AM approach.